Case Report: Metronidazole-induced encephalopathy in a patient with acute myeloid leukemia type 2 and a literature review of the pediatric case reports - Zhao, Chunyan; Zhang, Qingping; Zhang, Meijiao; Zhang, Jie; Bao, Xinhua (Frontiers in Pediatrics, 2025)
BackgroundMetronidazole exerts neurotoxic effects on the central nervous system, leading to rare pediatric cases of metronidazole-induced encephalopathy (MIE).MethodsThis study reports a pediatric patient with MIE. The patient's clinical and neuroimaging data was collected and analyzed. A literature review of pediatric MIE cases reported up to June 2025 was conducted using PubMed, Embase, Web of Science, Cochrane Library, WanFang, and CNKI databases.ResultsA 13-year-old female developed MIE after two courses of metronidazole with cumulative doses of 31.2 g and 37.6 g. Clinical manifestations included altered mental status, ophthalmoplegia, dysarthria, dysphagia, involuntary movements, dystonia, urinary retention, muscle weakness, and absent tendon reflexes. Brain MRI revealed T2W/FLAIR and DWI hyperintensities symmetrically involving the dentate nuclei, splenium of corpus callosum, basal ganglia, thalamus, midbrain, and pons. After discontinuing metronidazole and vitamin B1 therapy, the patient's symptoms gradually improved, though extrapyramidal symptoms persisted. Repeated brain MRI at 10 days after cessation showed lesions partially resolved. Literature review identified 18 pediatric MIE cases, totaling 19 cases including our case. Except for one infant case presenting with intermittent hypothermia, bradycardia, growth retardation, reduced activity, muscle weakness and hypotonia, the predominant neurological symptoms in the other 18 cases were ataxia (11/18), altered mental status (8/18), dysarthria (7/18), and epileptic seizures (5/18). Symmetric brain MRI lesions involving dentate nuclei (13/17), splenium of corpus callosum (9/17), midbrain (6/17), pons (5/17). Most patients (17/19) achieved complete clinical resolution and brain MRI improvement after metronidazole withdrawal.ConclusionPediatric MIE is rare and manifests with widespread neurological involvement, characterized by cerebellar dysfunction, altered mental status, and seizures. Brain MRI typically reveals symmetrical lesions in the dentate nuclei, splenium of corpus callosum, and midbrain. Timely drug discontinuation is critical for treatment, and most cases are reversible, though a few may leave neurological sequelae.